Spiking injuries out of volleyball: A review of injury countermeasures - Cassell, E. (Monach University, 2001)
The Australian Bureau of Statistics (ABS) estimates that in 1999-2000 approximately 150,000 Australians aged 18 years and older (including 46,000 Victorians) participated in organised and unorganised volleyball. Volleyball was ranked 26th in the table of most-played sports and physical activities by adults in Australia (22nd in the table for Victoria). There is no one comprehensive source of data on injury in volleyball in Victoria or elsewhere. Injury data were extracted from a range of sources for this review including the ABS, Victorian hospital admissions and emergency department databases and Australian and overseas published studies. The weight of evidence indicates that volleyball has a lower risk of injury than all football codes, basketball and some high-risk recreation activities, for example horse riding and skiing. Studies uniformly report that sprains and strains (predominantly ankle sprains) account for approximately twothirds or more volleyball injuries. The ankle, hand/finger, knee and shoulder are the most common sites of volleyball injuries. The overall aim of this report is to critically review the formal research literature and informal sources that describe measures to prevent volleyball injury and to assess the quality of evidence supporting claims of effectiveness. There are few formal evaluations of countermeasures to injury in volleyball so our review was extended to include countermeasures in other team ball sports that may be applicable to volleyball. Recommendations in this report include: extension of pre-participation evaluation; improvements to education and training for players and coaches, particularly at the wider community level; promotion of modified games for children; consideration of conditioning and exercise programs to prevent ankle and knee injuries (ankle disc and plyometric training); training in specific skills and techniques; use of ankle and finger taping and bracing; provision of appropriate and prompt first aid by trained personnel; improvements to injury data collections; and further epidemiological, biomechanical and laboratory research into the causes of volleyball injuries and measures to prevent them. Volleyball requires a variety of physical attributes (speed, power, flexibility, strength and balance) and specific playing skills. Therefore, participants need to train and prepare to meet at least a minimum set of physical, physiological and psychological requirements to cope with the demands of play and reduce the risk of injury.